Jews in a Graeco-Roman world - Goodman, Martin, 1953- (Clarendon Press ; Oxford University Press, 1998)
This book contains studies of the social, cultural, and religious history of the Jews in the Graeco-Roman world. Some of the sixteen contributors are specialists in Jewish history, others in classics. They tackle from different angles the extent to which Jews in this period differed from other peoples in the Mediterranean region, and how much Jewish evidence can be used for the history of the wider classical world.